Determination of Physical Fitness Index (PFI) among Female College Students - Tariq, Saffa; Solangi, Zohaib Anwar; Hamza, Ameer; Zamin Abbas Syed; Iftikhar, Ayesha; Sabir, Usama Bin; Hanan, Abdul (International Health Review, 2024)
Physical fitness/cardiovascular fitness is considered as the best reflection of whole-body health. It can be maintained by improving the physical fitness/cardiovascular fitness levels of individuals. The current study attempted to analyze the physical fitness index (PFI) of female college students by using the Harvard step test. A cross-sectional research was conducted from June 2021 to January 2022. Non-probability convenient sampling technique was employed to choose a sample of 340 students based on inclusion and exclusion criteria. Data was collected from Government Degree College for Women, Government Post-Graduate College for Women, and Apex College Sialkot, Pakistan. The data was entered and analyzed through SPSS. PFI scores showed students who had excellent and good scores, for instance 13 (3.8%) and 39 (11.5%), respectively. High average and low average scores were 172 (50.6%) and 62 (18.2%), respectively. Students who had poor scores were 54 (15.9%). The mean PFI was 66.91± 11.23, respectively. The association of PFI with BMI showed spearman correlation value as 0.136 with p-value < 0.05. The findings showed that most of the female college students had average to low PFI.